INTOLERANSI LAKTOSA - Wicaksono, Madya Ardi (MANDALA of Health, 2014)
Lactose intolerance is a condition caused by lactase deficiency in the brush border of the intestine, causing inability in digesting lactose into glucose and galactose. It is a mild metabolic disease with low morbidity, but often used interchangeably with cowâs milk allergy, resulting confusion in public understanding. Lactase deficiency keeps lactose not hydrolyzed, resulting increased osmotic pressure and fluid secretion of intestine lumen. In the colon, the result of fermentation from the undigested lactose is hydrogen gas.Â  The symptoms of lactose intolerance are abdominal bloating, distension, pain, flatulence, and diarrhea. Symptoms are alleviated by complete elimination or reduced consumption of lactose-containing foods. Meanwhile, dairy products which contain large amount of lactose also become the main source of calcium as well. Elimination of dairy products from daily diet may results low calcium level, osteopenia, until osteoporosis. People with lactose intolerance need calcium supplementation to maintain the calcium level in the body if lactose is restrictedÂ